GENUS CYTOSPORA Ehrenb. IN THE SOUTH-EAST OF KAZAKHSTAN (Experimental biology, 2023)
Information about pycnidial fungi of the southeast of Kazakhstan is insufficient and significantly outdated (especially the taxonomy of species), despite the fact that some of them are of great economic importance as parasites of woody plants. Therefore, the aim of our work was to identify species of the genus Cytospora Ehrenb. on the territory of the south-east of Kazakhstan and to analyze data on their distribution and range of host plants. The scientific and practical significance of the work lies in obtaining data on new localities of species of the genus Cytospora, which are of great importance as causative agents of cancer and peptic ulcer disease of woody host plants, leading to the death of tree branches. The material for the article was the authors' own collections carried out in different years, herbarium specimens stored in the herbarium of the Institute of Botany and Phytointroduction, as well as literary data. The preparation of fungi specimens, their study and identification were carried out according to the standard methods. The samples were studied and photographed using a Polyvar photomicroscope with Nomarsky interference optics. An annotated alphabetical list of species is provided with host plants and collection coordinates. Of the genus Cytospora, 43 species were found in the southeast of Kazakhstan. The maximum number of species (26) was found in the foothills of the Zailiysky Alatau, 20 species of Cytospora were noted in the Zailiysky Alatau, 10, 9 and 7 representatives of the genus, respectively, are typical for the mountain ranges of the Dzhungarsky Alatau, Kungei Alatau and Altyn-Emel. In the desert territories of the southeast of Kazakhstan, 8 species were found. Species of the genus Cytospora are found on representatives of vascular plants from 29 families. The largest number of species was recorded on the family Rosaceae Juss. (11 species), Salicaceae Mirb. (7), Betulaceae Gray (4), Fabaceae Lindl. (3 types). The value of the study and its practical significance lies in obtaining data on the location, distribution, and association with the host of Cytospora species.
Keywords: Pycnidial fungus, Cytosporosis, genus Cytospora, host plant, location, plant cancer, southeast of Kazakhstan.